Teacher Strategies to Improve Children's Learning Concentration in Qur'anic Memorization: A Cognitive and Self-Regulated Learning Perspective - Afidatus Sholihah; Lukman Sumarna; Siti Masruchah; Evi Afifah Hurriyati; Achmad Ushuluddin (Jurnal Impresi Indonesia, 2026)
Children’s learning concentration is a critical determinant of success in Qur’anic memorization (tahfiz), yet limited research has examined the cognitive mechanisms underlying concentration in this unique educational context. This research investigates tahfiz teacher strategies for enhancing children’s learning concentration from the perspective of cognitive psychology and Self-Regulated Learning (SRL) theory. Employing a qualitative, multi-site case study design, data were collected through in-depth interviews with tahfiz teachers (n = 8) at two institutions, participant observations over six months, and document analysis. Findings reveal four primary strategy domains: (1) attentional control strategies—including session segmentation, multisensory engagement, and environmental optimization; (2) working memory support strategies—including chunking, scaffolded repetition, and auditory–verbal rehearsal; (3) motivational regulation strategies—including intrinsic value cultivation, goal setting, progress monitoring, and social motivation; and (4) metacognitive development strategies—including self-monitoring training, reflective practice, and adaptive strategy use. The findings contribute to educational psychology by demonstrating how SRL principles operate in non-Western, memorization-based educational settings and by identifying practical, evidence-informed strategies for enhancing children’s concentration during cognitively demanding tasks.